Tradition as a Bridge Between Islam and Christianity in Kediri - Huda, M. Thoriqul; Muslihun, Muslihun; Lutfiana, Lela Ade (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
Tradition is a social practice that is inseparable from community life. It not only serves as a cultural heritage but also serves as a space for social interaction. In reality, tradition often acts as a bridge for dialogue between religious communities. Traditional practices allow individuals from different religious backgrounds to meet, interact, and build harmonious social relationships. In Kediri society, tradition serves as a means of bringing Muslims and Christians together in social life. The various traditions that develop in society are not solely followed by one religious group but often involve the participation of people from across religions. Joint participation in these traditions creates a natural space for dialogue, where values of togetherness, mutual respect, and tolerance can grow organically. This research on culture and interfaith harmony aims to comprehensively examine the role of tradition in the life of the multireligious community in Kediri. This research utilizes qualitative methods, including interviews, field observation and documentation, as well as data analysis using data reduction, data presentation, and conclusion drawing techniques. The results indicate that tradition, in addition to being understood as a theological practice, also serves as a medium for dialogue between Muslims and Christians in Kediri. The unduh -unduh tradition, part of the GKJW Christian liturgy, has played a crucial role as a bridge of harmony between Islam and Christianity. This finding of culture as a bridge for interfaith relations reinforces Hans Kung's theory of interfaith dialogue and Pierre Bourdeu's theory of culture as capital in habitus.